2019
DOI: 10.17509/mimbar-sd.v6i2.17040
|View full text |Cite
|
Sign up to set email alerts
|

Factors Responsible for Students’ Lateness to School as Expressed by Nigerian Teachers in Elementary Schools

Abstract: Students’ lateness to school is one of the challenges faced by school administrators. This research therefore investigated the factors responsible for students’ lateness to school as expressed by Nigerian teachers in elementary schools. The influence of moderating variables of sex, years of teaching experience and educational qualification on the respondents’ expressions was also considered. The study is descriptive in nature and sampled 200 Nigerian teachers in elementary schools. An instrument titled ‘Factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…Time management among students remains a signi cant problem that various learning institutions face. This is because it has an overwhelming effect on student learning processes which may negatively affect learning institutions and the students' grades as a result of poor performances in class, being absent in classes, showing irresponsible behaviours, and not being able to achieve their life goals because of poor time management (Adegunju, Ola-Alani & Agubosi, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Time management among students remains a signi cant problem that various learning institutions face. This is because it has an overwhelming effect on student learning processes which may negatively affect learning institutions and the students' grades as a result of poor performances in class, being absent in classes, showing irresponsible behaviours, and not being able to achieve their life goals because of poor time management (Adegunju, Ola-Alani & Agubosi, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…Poor time management is still increasing among students (Adegunju et al, 2019;Alio, 2015;Maile & Olowoyo, 2017). In addition, Jumare, Maina, and Ankoma-sey (2015) analyzed students' lateness in classes while Malcolm, Wilson, Davidson, and Kirk (2013) analyzed the causes of absenteeism in classes and punctuality as a recurring issue in secondary schools in South Africa (Onoyase, 2017).…”
Section: Problem Statementmentioning
confidence: 99%
“…Several studies have reported on the factors responsible for causing late coming among high school learners (Jumare et al, 2015;Onoyase, 2017: Maile & Olowoyo, 2017. A report compiled by Adegunju et al (2019) revealed that Nigerian teachers ascribed late coming to poor preparation for school, going to bed late, travelling distance between school and home, level of poverty, peer pressure, and single parenthood. Other studies identified household chores especially for girls from poorer, more rural households, who also often have to look after younger siblings or sick relatives as a major factor (Nonkonana & Kwenda, 2020;Adegunju, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A report compiled by Adegunju et al (2019) revealed that Nigerian teachers ascribed late coming to poor preparation for school, going to bed late, travelling distance between school and home, level of poverty, peer pressure, and single parenthood. Other studies identified household chores especially for girls from poorer, more rural households, who also often have to look after younger siblings or sick relatives as a major factor (Nonkonana & Kwenda, 2020;Adegunju, 2019). Maile and Olowoyo (2017) highlighted the lack of teaching materials, mode of delivery, first lesson of the day, and structure of the schools as reasons for late coming and absenteeism.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation